Graph colour-based resource allocation for relay-assisted D2D underlay communications - Liu, Miaomiao; Zhang, Li (IET communications, 2020)
Relay-assisted device-to-device (D2D) communications have been proposed as a supplement for direct D2D communications to enhance traffic offloading capacity. In this study, the authors propose a joint mode selection, relay selection and resource allocation for relay-assisted D2D communications. They aim at maximising the overall system throughput while guaranteeing the power limitation and signal-to-noise-and-interference ratios of all cellular and active D2D links. Since this optimisation is NP-hard, they then propose a graph colour-based resource allocation algorithm to effectively solve it. Simulation results show that the proposed algorithm can produce close-to-optimal performance with acceptable computational complexity.